A preliminary analysis of the distribution and spatial/temporal patterns of seabirds in the Laje de Santos Marine State Park (Santos, Brazil) and surrounding waters - Fey, Jésica Daniela [UNESP]; Neves, Tatiana da Silva; Baraldo, Kleber Barrionuevo [UNESP]; Peppes, Fabiano (FapUNIFESP (SciELO), 2017)
This study investigates the temporal taxonomic variation of the seabird community, and the spatial distributions of seabirds in the Laje de Santos Marine State Park (PEMLS) and surrounding waters, based on shipboard surveys. The increase in the number of seabird taxa during winter is associated to the presence of migratory birds from the south. During summer, only resident species were observed within the park. Analysis of the spatial distributions of taxa using geographic information systems (GIS) identified three different regions within the study area. The first was close to the coast, where birds interact with fishing activities in search for food; the second was the nesting area that provides shelter for the breeding colonies; and the third, which is farther offshore and more exposed, where a higher number of migratory birds were observed during winter surveys. The PEMLS and surrounding waters have characteristics that are important for the study and preservation of seabirds in Brazil and for the South Atlantic Ocean.
Keywords: Geo-processing; Laje de Santos Marine State Park; Seabirds; Seasonality; Spatial distribution